Leadership and Management Strategies in Chinese Higher Education on Attracting International Students: A Systematic Literature Review - Damayanthi, Natalina; Tukiran, Martinus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The purpose of this study is to identify and analyze the key factors driving international students to choose China as a study destination. The rapid increase in the number of international students in China in recent years indicates that the country holds strong appeal, academically, economically, and culturally. This research adopts a Systematic Literature Review (SLR) method, examines leadership and management strategies in Chinese higher education institutions (HEIs) to attract international students, focusing on key frameworks, policies, and practices. Using a systematic search methodology, eight empirical articles from reputable journals were analyzed to identify recurring themes and insights. Key findings reveal that Chinese HEIs leverage centralized, top-down management approaches to implement large-scale internationalization strategies while integrating service-oriented practices to enhance student experiences. Factors such as cultural diplomacy, reputation building, and the provision of scholarships and high-quality academic programs emerge as critical in attracting international students. This review also identifies challenges, including the need to balance academic quality and rapid enrollment growth, address cultural integration, and adapt to diverse student expectations. The findings contribute to a deeper understanding of how leadership and management strategies shape the internationalization of Chinese higher education and provide insights for future research, including the role of technology and comparative studies across regions. This study serves as a valuable resource for policymakers and institutional leaders seeking to enhance global engagement and competitiveness in higher education.